Complement-Independent Modulation of Influenza A Virus Infection by Factor H - Murugaiah, Valarmathy; Varghese, Praveen M.; Saleh, Soad M.; Tsolaki, Anthony G.; Alrokayan, Salman H.; Khan, Haseeb A.; Collison, Kate S.; Sim, Robert B.; Nal, Béatrice; Al-Mohanna, Futwan A.; Kishore, Uday (Frontiers in Immunology, 2020)
The complement system is an ancient innate immune defense mechanism that can recognize molecular patterns on the invading pathogens. Factor H, as an inhibitor of the alternative pathway, down-regulates complement activation on the host cell surface. Locally synthesized factor H at the site of infection/injury, including lungs, can act as a pattern recognition molecule without involving complement activation. Here, we report that factor H, a sialic acid binder, interacts with influenza A virus (IAV) and modulates IAV entry, as evident from down-regulation of matrix protein 1 (M1) in H1N1 subtype-infected cells and up-regulation of M1 expression in H3N2-infected A549 cells. Far-western blot revealed that factor H binds hemagglutinin (HA, ~70 kDa), neuraminidase (NA, ~60 kDa), and M1 (~25 kDa). IAV-induced transcriptional levels of IFN-α, TNF-α, IL-12, IL-6, IFN-α, and RANTES were reduced following factor H treatment for the H1N1 subtype at 6 h post-infection. However, for the H3N2 subtype, mRNA levels of these pro-inflammatory cytokines were enhanced. A recombinant form of vaccinia virus complement control protein (VCP), which like factor H, contains CCP modules and has complement-regulatory activity, mirrored the results obtained with factor H. Both factor H (25%), and VCP (45%) were found to reduce luciferase reporter activity in MDCK cells transduced with H1N1 pseudotyped lentiviral particles. Factor H (50%) and VCP (30%) enhanced the luciferase reporter activity for H3N2, suggesting an entry inhibitory role of factor H and VCP against H1N1, but not H3N2. Thus, factor H can modulate IAV infection and inflammatory responses, independent of its complement-related functions.